Diskriminasi Perempuan Dalam Media Baru (Analisis Semiotika Roland Barthes pada Tayangan Eksperimen Sosial Channel Youtube Zavilda TV) - Muriawan, Nie Gusti Madia (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Zavilda TV is a YouTube channel created by a veiled Muslim woman from Surabaya named Vilda Rosandi, but commonly known as Zavilda. Zavilda's youtube has 211 thousand subscribers with a total of 179 contents that have been uploaded since April 2021. The content produced by Zavilda is social experiment content related to hijab. Researchers used primary data in the form of three videos on Zavilda TV's youtube channel. This research uses a descriptive qualitative approach with Roland Barthes semiotic analysis to reveal meanings (denotative, connotative, myth). The three women in the social experiment show on the Zavilda TV Youtube channel are the targets and objects of social experiments who experience acts of discrimination both directly and digitally by Zavilda, because these women receive psychological intimidation, digital objectification, and coercion / pressure to agree to wear the hijab. The targeted women are also not treated as humans who are in full control of their autonomy, as they are used as Zavilda TV's main commodity solely for profit. This can be seen from the selection of titles, thumbnails, and video content that focuses on women's bodies and uses sensual words. This is an act of discrimination against women because it violates their right to freedom of expression and religion and violates their right to privacy and autonomy. Therefore, the researcher has concluded that discrimination of women in new media is still a problem because it is not only done by the opposite sex, but discrimination can also be obtained from fellow women.